2020
DOI: 10.21833/ijaas.2020.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution for heat transfer of Oldroyd–B fluid over a stretching sheet using successive linearization method

Abstract: The objective of this study is to find the numerical solution for the MHD flow of heat transfer to the incompressible Oldroyd-B liquid on a stretching sheet channel. The partial differential equations governing this system are converted into ordinary differential equations using similarity conversion. The resulting nonlinear equations governing the flow problem are numerically solved by the successive line method (SLM). Numerical results are derived and presented in tables for some comparisons. These compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 33 publications
(52 reference statements)
3
10
0
Order By: Relevance
“…Here, we test the validity of our numerical results and contrast them with those of published works as limiting examples. So, we contrast the outcomes of this study with those found in the literature (Ghadikolaei et al, 2018;Salah and Elhafian, 2019;Noor, 2012;Shateyi, 2013). It is found that our results are in excellent agreement with Noor (2012) and Shateyi (2013) as shown in Tables 2-5.…”
Section: Numerical Scheme Testingsupporting
confidence: 58%
See 2 more Smart Citations
“…Here, we test the validity of our numerical results and contrast them with those of published works as limiting examples. So, we contrast the outcomes of this study with those found in the literature (Ghadikolaei et al, 2018;Salah and Elhafian, 2019;Noor, 2012;Shateyi, 2013). It is found that our results are in excellent agreement with Noor (2012) and Shateyi (2013) as shown in Tables 2-5.…”
Section: Numerical Scheme Testingsupporting
confidence: 58%
“…The SLM technique presupposes that the solution of system of Eqs. 13-15 can be represented as (Salah et al, 2023;Ahmed et al, 2016;Salah and Elhafian, 2019):…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stretched surface is given a magnetic field that is consistently consistent and uniform in a normal direction. Under the constant and boundary layer assumptions, the continuous constitutive equation of the Oldroyd-B fluid and energy equation is presented below [42][43][44]:…”
Section: Governing Equations and Boundary Conditionsmentioning
confidence: 99%
“…Gupta et al 18 deliberated flow of second grade non Newtonian fluid over stretching plane. Salah and Elhafian 19 studied flow of non-Newtonian second grade fluid on an extending surface using a numerical technique. Hayat et al 20 explored Maxwell fluid flow on moving sheet of unequal thickness.…”
Section: Introductionmentioning
confidence: 99%